PENERAPAN TEORI BELAJAR BEHAVIORISTIK UNTUK MEMBENTUK KARAKTER DISIPLIN BELAJAR - Titik Widayati; Mutiara Annisa (Universitas Muhammadiyah Klaten, 2026)
Education is a crucial process that involves individual transformation in response to stimuli. In learning, the teaching method commonly used is Behaviorist Theory. Thepurpose of this article is to explore various ways of applying behaviorist learning theory in the context of learning. This research adopts a qualitative approach through literature study or literature review. The results show that behaviorist theory can be used in teaching in schools, including providing stimulation and response to students, encouraging positive behavior, and rewarding students who are disciplined. The principles of behaviorism, such as providing stimulus and response and facilitating imitation, have been proven to overcome discipline problems and encourage effective learning.